রামকৃষ্ণচর্চা ১৮০র আভিমুখে - (:unkn) unknown (Sutradhar Publication, 2015)
Sri Ramakrishna is the infinite wonder of human civilization. This book is an attempt to explore the depths of this inevitable man in historical chronology.
Ramakrishna Charcha : Eksho Ashir Abhimukhe
Keywords: Bengali; Literature; Bengali; Bengali